Thermal performance enhancement of a heat exchanger using metal chain as a novel turbulator - Ghitheeth, Ali Hussein (2021)
Enhancing heat transfer in a heat exchanger system is critical to many industrial applications. There are many problems that require in-depth studies to find solutions. One of the main problems is the poor heat transfer rate, due to the fluid flow behavior inside the tubes, and to increase the heat transfer rate, the flow behavior inside the heat exchanger tubes must be changed. This study presents an experimental and numerical approach to enhance heat transfer in a heat exchanger tube using new types of turbulator (metal chains) inserted in the heat exchanger tube to change the flow behavior. Fifteen (15) configurations of metal chains were tested; three ratios of the wire diameter/tube diameter, (t/D = 0.1, 0.15 and 0.2), with five lengths of the chainrings represented by the ring length/tube diameter, (P/D = 1, 2, 3, 4 and 5). The experimental system (test rig) consisted of a 2000 mm thermal insulated carbon steel tube exchanger test section, in which the inner and outer diameters were 20 mm and 26 mm respectively. The fluid used was heavy fuel oil, with a fully developed turbulent flow, Reynolds number, (Re = 5000 to 15000), and uniform heat flux on the external wall of 6000-Watt. A 3D computational fluid dynamics calculation was also made to study the effect of metal chains on the fluid flow behavior inside the tubes on the overall thermal performance. Both experimental and simulation results showed that the insertion of the metal chain into the heat exchanger tube increases the thermal performance factor (η), the Nusselt number (Nu), and the friction factor (f). The thermal performance factor (η) decreased with the increase in Reynolds number for all cases. The highest thermal performance factor (η) was found at t/D = 0.15 and P/D = 3, while both the highest Nusselt number (Nu) and friction factor (f) were found at t/D = 0.2 and t/D = 1. The numerical study unveiled that the use of metal chains inside the tube leads to path changes and splits in the fluid flow. It is crucial to generate large longitudinal and transverse vortices inside the tube. These vortices play a substantial role in enhancing heat transfer.